The Moderating Role of Merger on the Switching Intention to Use Islamic Bank: The Case of Indonesia - Matsahri, Matsahri; Widiastuti, Tika; Masrizal, Masrizal; Mawardi, Imron; Atiya, Nikmatul; Sadikin, Muhamat Ali (Universitas Syiah Kuala, 2024)
Objective Since February 2021, the government decided to merge 3 Islamic banks to increase Islamic bank markets. This policy raises pros and cons in society. This research analyses the mediating role of mergers on the switching intention to use Islamic banks.Design/Methodology This research is a quantitative study using the Structural Equation Model Partial Least Square (SEM-PLS). A total of 108 respondents' data were analyzed. The data was collected through an online survey utilizing social media which was shared directly with respondents in the city of Surabaya. The respondents' criteria were selected using purposive sampling techniques.Results The moderating effects showed that the merger was a poor moderator of the reality between attitude, subjective norms, and perceived behavioral control on the switching intention to use Islamic banks. However, the direct effects showed a significant relationship between mergers and switching intention. Besides, this study shows that attitude, subjective norm, and perceived behavioral control have a significant influence on switching intention. Subjective norm is the most dominant factor.Research limitation/implication This study uses limited variables and was carried out shortly after the merger of Islamic banks. However, this study provides a comprehensive analysis related to the relationship between mergers and switching intention. The implications of this research urge the government as a policymaker to do its best to increase public awareness of Islamic banks. Islamic bank managers must conduct massive socialization by utilizing various existing technologies and media to reach all levels of society to use Islamic banking services.Contribution This study emphasizes the significance influence of subjective norm and switching intention. Thus, the government and Islamic banks must intensify socialization of Islamic bank to encourage Islamic bank users.Novelty/Originality This study complements the literature by analysing the impact of Islamic bank mergers with switching intention to use Islamic banks as far as the authors' knowledge of merger research is still limited to analysing the performance of Islamic banks after the merger.